Evaluating the Durability of Lime-Stabilized Soil Mixtures using Soil Mineralogy and Computational Geochemistry. Issue 9 (September 2021) - Akula, Pavan; Naik, Saureen Rajesh; Little, Dallas N.
Lime stabilization is a common technique used to improve the engineering properties of clayey soils. The process of lime stabilization can be split into two parts. First, the mobilization and crowding ofC a 2 + ions orCa ( OH ) 2 molecules from hydrated lime at net negative surface charge sites on expansive clay colloids. Second, the formation of pozzolanic products including calcium-silicate-hydrate (C-S-H) because of reactions within lime-soil mixtures. The pozzolanic reaction is generally considered to be more durable, while thecalcium adsorption has been associated with more easily reversible consistency changes. This study offers a protocol to assess whether the stabilization process is dominated by durable C-S-H (pozzolanic) reactions or a combination of cation exchange and pozzolanic reactions. Expansive clays with plasticity indices >45% from a major highway project in Texas are the focus of lime treatment in this study. The protocol consists of subjecting lime-soil mixtures to a reasonable curing period followed by a rigorous but realistic durability test and investigating the quality and quantity of the pozzolanic reaction product. Mineralogical analyses using quantitative X-ray diffraction (XRD) and thermogravimetric analysis (TGA) indicates the formation of different forms of C-S-H. In addition, geochemical modeling is used to simulate the lime-soil reactions and evaluate the effect of pH on the stability of C-S-H. The results indicate C-S-H with Ca/Si ratio of 0.66 as most the stable form of C-S-H among other forms with Ca/Si ratio ranging from 0.66 to 2.25. The effect of reducing equilibrium pH on C-S-H is also evaluated. A reduction in pH favored dissolution of all forms of C-S-H indicating the need to maintain a pH ≥ 10.